Research on the impact of green finance development on energy intensity in China - An, Qiguang; Lin, Chengwei; Li, Qingzhao; Zheng, Lin (Frontiers in Earth Science, 2023)
China has accelerated its energy transition to help achieve carbon peaking and neutrality. This resulted in significant investment and financial demand, and green finance has developed into a potent tool to support energy transition. A thorough examination of how green financial development affects energy intensity is urgently needed to achieve sustainable development and combat climate change. This study investigated the effects of green finance development on energy intensity using Chinese provincial panel data from 2007 to 2019. The findings indicate that green finance development significantly lowers energy intensity, in which industrial structure upgrading plays a mediating role. Based on the threshold effect, when the green finance index rises above 0.199, the effect of reducing energy intensity becomes significant and exhibits a nonlinear feature of diminishing marginal effect. By examining the spatial spillover effect, the analysis shows that the development of green finance not only reduces the energy intensity of the region but also reduces the energy intensity of neighboring regions. Based on these findings, we proposed regionally targeted and differentiated green finance development policies to reduce energy intensity as soon as possible and assist in reaching carbon neutrality.